Kemenangan Benyamin Davnie dan Pilar Saga Ichsan di Pilkada Tangerang Selata Tahun 2020 Masa Pandemi Covid-19 - Gustamar Gustamar; Julian Adrin Pasha (Journal of Politics and Democracy, 2021)
The electoral success of incumbent Benyamin Davnie and Pilar Saga Ichsan in the 2020 Tangerang Selatan mayoral election, conducted during the COVID-19 pandemic, presents an interesting case. Despite mobility restrictions and assumptions that incumbents benefited from the pandemic situation, not all incumbents contesting the 2020 local elections were re-elected. One notable case is Benyamin Davnie, who, after serving two terms as deputy mayor, managed to extend his political influence by running for mayor alongside Pilar Saga Ichsan, supported solely by the Golkar Party. This study draws upon Bourdieu’s theory of capital, Schroder’s concept of political strategy, and Rackway’s campaign model to examine the key factors contributing to their electoral achievement.